The ideation of modeboro upcycling outfit on boro sashiko technique for eco-friendly production - Roslan, Muhammad Iqmal; Ahmad, Hasma (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
Societies around the globe have been consuming more clothes over the last decades and fast fashion has taken center stage to fulfil the rising demand which eventually contributes to the environmental impact of clothing waste. The purpose of this project is to utilize the ideation of Boro Sashiko technique that emphasizes upcycling, repair, and reuse in modular design exploration concept to further support sustainability by creating versatile garments that can be customized, repaired, and repurposed, reducing the need to produce new items constantly. The project also tackles commercialization potential through usability tests to obtain user validation while determining market acceptance. MODEBoro features the emergence of “Lazy Wear” as a form of easy making-up process and serves as a blueprint for future ready-to-wear collections. Ultimately, MODEBoro highlights the prospective for Boro Sashiko and modularity to shape the future of sustainable fashion, offering a pathway toward a more environmentally conscious, enhanced well-being and culturally enriched industry.